(untitled) (Bangladesh Journal of Botany, 2025)
The present study explored morphometric relationships of 24 species belonging to 14 genera of Anacardiaceae (R. Br.) Lindl. for the very first time in Bangladesh, using a numerical systematic approach. A total of 33 vegetative and reproductive characters were analyzed through cluster analysis (CA) and principal component analysis (PCA). The UPGMA dendrogram revealed two major clades, comprising 18 and six species, respectively. In the first clade, Mangifera indica and M. longipes (tribe Anacardieae) exhibited the highest similarity, while in the second clade, the highest affinity was found between Spondias dulcis and S. pinnata (tribe Spondiadeae). PCA explained 85.70% cumulative variance across the first six principal components, with scatter and projection plots aligning with the cluster analysis results. These findings provide the insights into the taxonomic relationships of Anacardiaceae in Bangladesh, aiding conservation strategies, particularly for threatened and medicinally important species, and serving as a foundation for future molecular phylogenetic endeavor. Bangladesh J. Bot. 54(2): 199-209, 2025 (June)